CLINICAL AND ANGIOGRAPHIC SPECTRUM AMONG CASES WITH LEFT MAIN CORONARY ARTERY DISEASE - DASH, BIJAY KUMAR; MOHANTY, NIRMAL KUMAR; ROUT, PRAMOD KUMAR; SATYANARAYANROUTRAY; VASANTABARAI, RAHUL (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Left main coronary artery disease (LMCA) is a significant threat factor for amplified morbidity and mortality in the analysis and treatment plan of coronary artery disease. Multivessel disease of other coronary arteries is seen in 80% of patients with left main disease. With drug-eluting stents and advances in percutaneous coronary intervention, the management of this disease is not purely surgical. Hence, angiographic profile of patients with left main coronary artery stenosis was evaluated. Methods: A total of 700 cases of significant coronary arterial disease clinical and those underwent coronary angiography were studied and their coronary angiogram was analyzed with respect to pattern of involvement. Results: Of these cases, 72 patients have LMCA disease of those 24 cases have obstructive and 48 cases have non-obstructive disease and among them, 63.9% were diabetic; 55.5% were hypertensive, 44.4% have dyslipidemia, and 48.6% were smokers. Mean age was 56.5 years and mode of presentation was non-ST-elevation myocardial infarction (STEMI) in 59.7%; CSA in 30.5%, and STEMI in 9.7% cases. Distal left main was most common involvement in 79.2% cases of which 61.1% have bifurcation and 18.1% have non-bifurcation lesions. Isolated ostial involvement is seen only in 6 patients. 93% had involvement of other coronary arteries, 9.7% had SVS; 22% had DVD; and 61% had TVD. Conclusion: Overall, the incidence of LMCA disease was 10.2% and 3.4% had only significant obstructive lesion. Distal bifurcation was the most common form of involvement and TVD was reported to be the most common association.